PERBEDAAN PENURUNAN TINGGI FUNDUS UTERI SETELAH PEMBERIAN JUS NANAS PADA IBU POST PARTUM DI KABUPATEN KLATEN - Rahayu, Ripniatin Darmining (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Physiological changes that occur in the postpartum period is the contraction of the uterus, a process kemabalinya uterus to its original condition or pre-pregnant uterus manner. High penurrunan fundus process starts on the delivery of the placenta, if this process fails then called sub involusio, so it will trigger bleeding in the postpartum period. Subinvolusio is high congestion or delays decrease fundus accompanied by lengthening the period of expenditure lokhea or bleeding a lot and irregular. The uterus is palpable soft and larger than normal. Objective: to know the difference in height of the fundus uteri decrease after administration of pineapple juice in postpartum mothers. This study is a type of pre-experimental study with case-control study design group comparison. Population is Post-partum womens. Sample by means of non-probability sampling is jademental or sampling based on consideration of the researchers, the samples (22 mothers post partum). (Analysis data was performed with the independent samples t test). The results of the data analysis by the Independent Sample t test gain tcount 3,283 with probability (p) = 0.003, while ttable at 5% significance level (df = 30) was 2.042. Due tcount> t table (3.283> 2.042) with p <0.05 then there is a distinction between the reduction in TFU experimental and control groups. The average value of the TFU decrease in the experimental group reached 9.55 cm higher than the average TFU decline in the control group, which only reached 4.90 cm. This indicates that the administration of pineapple juice has a significant effect on the decline in TFU on postpartum mothers. Keywords: Difference decrease uterine fundus, pineapple juice.